Research on deterministic networking technology for space-ground integrated - Yuman ZHANG; Xia ZHU; Guoxin LIANG; Jiaen ZHOU; Yafei ZHAO; Mugen PENG (Dianxin kexue)
Satellite communication is a critical technology in the future of the communication field.Low earth orbit Internet constellations is a strategic infrastructure for the 6G integrated space-air-ground-maritime networks, which is capable of expanding the current communication network to the global near-earth region.Deterministic networking technology is a key component of space-based network, compared with the traditional best-effort packet network, it has the advantages of low latency, low jitter, low packet loss rate, and high reliability.Firstly, the current research background and status of deterministic networking were summarized, and then a deterministic networking architecture for satellite communications was proposed and its key technologies were described.Finally, the outlook for future research directions was discussed.